2005
DOI: 10.1007/s00213-005-2143-4
|View full text |Cite
|
Sign up to set email alerts
|

The antinociceptive and anxiolytic-like effects of the metabotropic glutamate receptor 5 (mGluR5) antagonists, MPEP and MTEP, and the mGluR1 antagonist, LY456236, in rodents: a comparison of efficacy and side-effect profiles

Abstract: Both mGluR5 and mGluR1 antagonists are effective in models of pain and anxiety. However, an mGluR1 antagonist was more efficacious than the two mGluR5 antagonists in the pain models, which, conversely, appeared more efficacious in the anxiety models. These findings support the potential utility of mGluR5 and mGluR1 antagonists for both the treatment of chronic pain and as novel anxiolytics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 50 publications
10
98
0
3
Order By: Relevance
“…On the other hand, it could be suspected that the decreased levels of social interaction might have been indirectly caused by anxiogenic effects of the compounds, as all of them decreased exploration of the central zone of the arena. It seems, however, to be unlikely, as NMDA receptor antagonists have been found to possess rather anxiolytic than anxiogenic properties (Xie and Commissaris, 1992), and MTEP has been shown to display anxiolytic-like activity in a number of animal models of anxiety (Busse et al, 2004;Varty et al, 2005). There is rather a direct consequence of concomitantly present stereotyped behaviors manifested in walking in the periphery of an open field arena.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it could be suspected that the decreased levels of social interaction might have been indirectly caused by anxiogenic effects of the compounds, as all of them decreased exploration of the central zone of the arena. It seems, however, to be unlikely, as NMDA receptor antagonists have been found to possess rather anxiolytic than anxiogenic properties (Xie and Commissaris, 1992), and MTEP has been shown to display anxiolytic-like activity in a number of animal models of anxiety (Busse et al, 2004;Varty et al, 2005). There is rather a direct consequence of concomitantly present stereotyped behaviors manifested in walking in the periphery of an open field arena.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of MPEP and MTEP reduced hyperalgesia induced by formalin and mechanical allodynia following SNL and showed anxiolytic effects (203).…”
Section: Nociceptionmentioning
confidence: 98%
“…Both MPEP and MTEP were also tested in the mouse formalin and rat spinal nerve ligation (SNL) pain models, as well as in anxiety models including the Vogel conflict and conditioned lick suppression (CLS) tests for anxiety (203). Systemic administration of MPEP and MTEP reduced hyperalgesia induced by formalin and mechanical allodynia following SNL and showed anxiolytic effects (203).…”
Section: Nociceptionmentioning
confidence: 99%
“…Various studies examining the behavioral effects of MPEP and MTEP in animal models of CNS disorders have demonstrated positive effects after acute systemic administration (c.f., Brodkin et al, 2002b;Chiamulera et al, 2001;Pietraszek et al, 2005;Spooren et al, 2000;Tatarczynska et al, 2001;Tessari et al, 2004;Varty et al, 2005). However, some investigators have reported that multiple dosing procedures with these compounds produces increases efficacy in the anxiolytic, antidepressant or anti-addictive effects as compared with acute administration (Backstrom et al, 2004;Cowen et al, 2005;Klodzinska et al, 2004;Li et al, 2006;Nordquist et al, 2007;Pilc et al, 2002).…”
Section: Discussionmentioning
confidence: 99%